Kedudukan Pemilik Merek Terdaftar alam Sengketa Kekayaan Intelektual: Kajian Asas Priorin Tempora Nelior In Jure Berdasarkan Putusan NO. 1291 K/PDT.SUS-HKI/2023 - Dita Safitri Nurwidihantari; Dewi Sulistianingsih (Universitas Wahid Hasyim, 2025)
Trademark protection is a crucial element within the Intellectual Property Rights (IPR) system, aimed at ensuring legal certainty while safeguarding the existence and reputation of a product or service. In Indonesia, trademark protection follows the first to file principle, whereby rights are granted to the party who first registers the trademark officially, regardless of prior usage. However, this system often gives rise to legal disputes, particularly when registration is carried out by unauthorized parties or with bad faith. This research specifically examines the Supreme Court of the Republic of Indonesia Decision Number 1291 K/Pdt.Sus-HKI/2023 in a dispute between Nitron Japan Co., Ltd., the original owner of the international trademark